Research on the thermo-hydraulic response characteristics of pore-fissure media using mixed finite volume method - Hongdan Yu; Chen Lu; Weizhong Chen; Luyu Wang; Jingqiang Yuan (Case Studies in Thermal Engineering, 2022)
After lengthy diagenesis and tectonic movement, a rock mass inevitably develops many pores and micro-fissures. A numerical simulation method was employed to study the thermal response characteristics of the rock mass under temperature seepage coupling by treating it as a pore-fissure medium and considering its anisotropic properties. Based on the mixed finite volume method (FVM), a numerical scheme of the governing equation for the temperature seepage coupling of the pore-fissure medium is derived, with the program solution module independently written in C++. On this basis, a numerical test model of the fissured mudstone is established to analyze the distribution of the rock mass temperature field under various thermal conductivities and the influence of fissure permeability on the seepage field. The mixed FVM results revealed that the temperature and water pressure distributions near the fissure were closely related to the directionality of thermal conductivity in the rock mass, as well as the thermal conductivity and permeability coefficient, respectively, of the fissure itself. Comparison with results from the finite element software ABAQUS demonstrated significant advantages of the proposed method when solving temperature and seepage problems in discontinuous geological bodies containing hiatuses, mutations, and fissures.